ORGANIZATIONAL BEHAVIOR OF SCHOOL HEADS AND ORGANIZATIONAL COMMITMENT OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN THE DISTRICT OF PILAR - Lozada, Remia F. (President University, 2024)
The way school administrators behave in an organizational capacity is vital to influencingteachers' organizational commitment and, eventually, the standard of instruction transmittedto the school community. The study aimed to determine the level of organizational behavior ofschool heads and the degree of organizational commitment of public elementary schoolteachers in the District of Pilar for the S.Y. 2023-2024. The respondents of the study were the160 elementary school teachers. Foreign and local literatures related to the study werereviewed in relation to their relevance and implications to the study. A validated and reliabilitytested researcher-made questionnaire was used to gather the needed data from the randomlyselected respondents. The statistical tools employed to analyze and interpret the data gatheredwere the frequency count, mean, t-test, ANOVA and Pearson r. The findings of the studyrevealed that the level of organizational behavior of school heads and the degree oforganizational commitment of teachers were “very high”. No significant differences werefound in the level of organizational behavior of school heads and the degree of organizationalcommitment of teachers when respondents were grouped according to sex, civil status, highesteducational attainment, and length of service. However, a significant relationship was foundbetween the organizational behavior of school heads and the organizational commitment ofpublic elementary school teachers. Open and transparent communication may be developedbetween school heads and teachers. This may not only enhance the quality of decisions, butalso reinforces a sense of community and commitment.